A Ten-year History of the Demography and Productivity of an Arctic Wolf Pack - Mech, L. David (ARCTIC, 1995)
A pack of two to eight adult wolves (Canis lupus arctos) and their pups was observed during ten summers (1986-95) on Ellesmere Island, Northwest Territories, Canada. The author habituated the wolf pack to his presence in the first summer and reinforced the habituation each summer thereafter. The first alpha female produced four to six pups each year between 1986 and 1989. However, her daughter, who succeeded her as the alpha female, produced only one to three pups each year between 1990 and 1992 and in 1994, and apparently did not whelp in 1993 or in 1995. The tenure of the first alpha male was at least two years, and his successor was alpha male for the remaining eight years of the study. The wolf pack was characterized by highly variable annual productivity. The second alpha male-and-female breeding pair likely was an older brother and a younger sister. Early survival of wolf pups was high and constant, with all pups surviving through August of their first year. The pack's demography was consistent with what is known for wolf packs in other regions of North America, but its productivity was more typical of arctic packs.Key words: wolf, Canis lupus, productivity, demography, breeding tenure, survival On a observé une bande comprenant de deux à huit loups adultes (Canis lupus arctos) et leurs louveteaux au cours de dix étés (1986-95), dans l'île d'Ellesmere située dans les Territoires du Nord-Ouest au Canada. L'auteur a accoutumé la bande à sa présence durant le premier été et a renforcé l'accoutumance durant chaque été subséquent. La première femelle alpha a produit de quatre à six louveteaux chaque année entre 1986 et 1989. Cependant, sa fille, qui lui a succédé en tant que femelle alpha, a produit seulement de un à trois louveteaux chaque année entre 1990 et 1992 et en 1994, et n'a apparemment pas mis bas en 1993 ni en 1995. Le premier mâle alpha a conservé son statut au moins deux ans, et son successeur a été le mâle alpha durant les huit autres années de l'étude. La bande de loups était caractérisée par ...